Results From a Non-Randomized Pilot Study Evaluating the Impact of a Novel Group Treatment Program Targeting Aggressive Script Rehearsal and Emotion Regulation in a Sample of Incarcerated Males - Morrison, Fiona P. (International journal of offender therapy and comparative criminology, 2024)
This study compared the efficacy of a novel group-based aggressive script rehearsal treatment program with an emotion regulation program. Participants were 48 incarcerated adult males (28 in the script rehearsal program and 20 in the emotion regulation program). Outcomes, including the frequency of aggressive script rehearsal, aggressive behavior, and emotion regulation difficulties, were measured pre-and post-treatment and at 46 days (on average) after treatment completion, and 104 days (on average) following treatment completion. Linear Mixed Model analyses revealed no significant difference in the frequency of script rehearsal overtime for either program. There was a significant reduction in aggressive behavior associated with the script rehearsal program and a reduction in emotion regulation difficulties for both programs. Future iterations of this aggressive script rehearsal treatment program may benefit from greater intensity and incorporation of strategies that address the many cognitive, affective, and situational factors that trigger and maintain aggressive scripts.